KEPUASAN PENGGUNA APLIKASI GRAB: STUDI EMPIRIS TERHADAP PENGARUH KUALITAS DAN RESPONSIVITAS LAYANAN CUSTOMER SERVICE MAHASISWA FAKULTAS EKONOMI UNIVERSITAS NEGERI MEDAN - Lubis, Adelina; Effendi, Ihsan; Kristin, Okta Viani; Lubis, Nabila Boru (Jurnal Manajemen dan Bisnis, 2025)
This study aims to analyze the influence of customer service quality and customer service responsiveness on user satisfaction with the Grab application among students of the Faculty of Economics at Universitas Negeri Medan. The background of this research stems from the increasing use of online transportation services, which demands excellent service quality, including interactions with customer service. The study employs a quantitative approach with simple random sampling techniques involving 100 respondents, and data analysis is conducted using SPSS version 26. The results reveal that customer service quality and customer service responsiveness significantly influence user satisfaction, both partially and simultaneously. Customer service responsiveness is identified as the most dominant factor, with a regression coefficient of 0.593, compared to customer service quality, which has a coefficient of 0.319. The coefficient of determination (R²) value is 0.412, indicating that 41.2% of the variation in user satisfaction can be explained by the two independent variables. These findings emphasize the importance of improving service quality and responsiveness to enhance user satisfaction and foster customer loyalty in digital application-based services such as Grab.